PENGEMBANGAN MEDIA PEMBELAJARAN FISIKA BERBASIS MULTIMEDIA PADA KONSEP MEKANIKA DI KELAS X SMA N 2 PADANG - Febrianda Rusfa (PILLAR OF PHYSICS EDUCATION, 2014)
Learning media is everything that used to stimulate student’s mind, feeling, attention and motivation so that can push learning process. Used of learning media based on computer hopelly can visualization something abstract in physics so that can help teachers and students in interactive learning process use Macromedia flash 8 proffesional. This research is aim  to produce source lesson such as learning interactive media using Macromedia flash 8 proffesional in valid and practice mechanics concepts. This research is Research and Development (R & D) research. This object is interactive learning media using Macromedia flash 8 proffesional. Data collection instrument in this research is professional sheet validation and practicality sheet for teachers and students. Used of data analitycal technic is descriptive analyze. From this analyze of proffesional sheet validation find validation value 87,47, sedangkan nilai praktikalitas dari siswa mendapatkan nilai 80,1. Based on analize theory  using  metoda grafik method, validation value and practicallity of this learning media classified in very good criteria